PENGEMBANGAN BAHAN AJAR KIMIA ORGANIK BERBANTUAN MEDIA KOMPUTASI TERHADAP KEMAMPUAN BERPIKIR KREATIF - Hulyadi Hulyadi; Khusnul Khotimah (Universitas Pendidikan Mandalika Mataram, 2016)
The results of observations and interviews on lecturers and students show that students tend to pay less attention when the lecturer explains the material. The interaction is also still impressed one way, only lecturers to students. It shows that students' interest toward organic chemistry learning is still low and considered difficult by them. Students are less directed in constructing their knowledge, resulting in many misconceptions and low student's thinking ability. This happens because the union has not multi-level chemical representation that includes the macroscopic, microscopic and symbolic levels in the learning process undertaken. This research was conducted on chemical education students at IKIP Mataram who took organic chemistry course II. This research was conducted from September to December 2016 consisting of preliminary research, product trial, data processing and preparation of research result report. This study aims to determine the feasibility and effectiveness of teaching materials with inquiry assisted approach Computational Chemistry program in improving students' creative thinking ability. This research uses R & D procedure which includes define, design and develop stage. The result of the research shows that the teaching materials developed meet the valid criteria, and effectiveness in improving the ability of creative thinking this can be seen from the result of the n-gain test which shows the improvement of students' creative thinking ability after learning using inquiry materials of computational media in organic chemistry.